The effect of social support on marital adjustment in hospital staff: The mediating role of self-control and resilience - Hamidreza Ishaqi Jardavi; Mahmoud Jajarmi; Hamzeh Akbari (Shahid Beheshti University of Medical Sciences, 2022)
Background: Marital adjustment is one of the most important factors in determining the stability and permanence of the marital relationship and can leads to feelings of happiness, satisfaction and satisfaction of needs that are mutually met. The aim of this study was to investigate the role of social support on marital adjustment in hospital staff with the mediating role of self-control and resilience. Methods: The present study was a descriptive correlational study. The statistical population included the staff of Samen Al-Aimeh Hospital in Mashhad with a total of 380 people in 2020, from which a sample of 257 married male and female staff were purposefully selected. Data were collected using questionnaires of social support, marital adjustment, resistance, and self-control. Data analysis was performed using SPSS software version 21 and Pearson correlation (structural equation type). Results: There was a significant relationship between self-control as a mediating variable and marital adjustment with value (B = 0.700, P <0.001). Also, there was a significant relationship between resilience as a mediating variable and marital adjustment with the amount (B = -0.643, P <0.001). A total of 0.93 variance related to marital adjustment was explained by the variables of social support, resilience and self-control. Conclusion: The results showed that social support has a positive effect on marital adjustment. It is recommended that in order to improve the marital adjustment of couples, workshops should be held on how to perform and receive social support and promote psychological flexibility in social organizations and institutions.